2017
DOI: 10.3390/v9100299
|View full text |Cite
|
Sign up to set email alerts
|

Seed Transmission of Beet Curly Top Virus and Beet Curly Top Iran Virus in a Local Cultivar of Petunia in Iran

Abstract: Beet curly top virus (BCTV) and beet curly top Iran virus (BCTIV) are known as the causal agents of curly top disease in beet and several other dicotyledonous plants in Iran. These viruses are transmitted by Circulifer species, and until now, there has been no confirmed report of their seed transmission. A percentage (38.2–78.0%) of the seedlings developed from the seeds of a petunia local cultivar under insect-free conditions showed stunting, interveinal chlorosis, leaf curling, and vein swelling symptoms, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 22 publications
1
12
0
1
Order By: Relevance
“…Another possibility is that the same ALCV variant may have been introduced throughout Argentina in infected planting material such as seeds. Although seed-transmission has never been demonstrated for capulaviruses, this scenario cannot be completely ruled out as several recent studies have confirmed that geminiviruses belonging to at least three genera ( Begomovirus , Becurtovirus , and Curtovirus ) can be seed-transmitted [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another possibility is that the same ALCV variant may have been introduced throughout Argentina in infected planting material such as seeds. Although seed-transmission has never been demonstrated for capulaviruses, this scenario cannot be completely ruled out as several recent studies have confirmed that geminiviruses belonging to at least three genera ( Begomovirus , Becurtovirus , and Curtovirus ) can be seed-transmitted [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…BCTIV is transmitted by the leafhopper Circulifer haematoceps in a circulative non-propagative manner, where the virus circulates through the insect body and accumulates in the salivary glands 21 . Due to the polyphagous behavior of this vector and the wide host range of BCTIV 11,2224 , encapsidated minicircles could be exported over a wide range of plants, similarly to defective DNAs 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Cells 2021, 10, x FOR PEER REVIEW 2 of 10 elucidate geminivirus origin, evolution and distribution patterns [11]. Furthermore, the seed transmissibility of TYLCV, one of the agents of the tomato yellow leaf curl disease (TYLCD) in tomato crops, has been pointed out as an additive factor that hampers the management of the disease, coupled with the increased presence of its vector, the whitefly Bemisia tabaci [5].…”
Section: Preparation Of Biological Materialsmentioning
confidence: 99%